2019
DOI: 10.3390/su11113211
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nutrient-Enriched Biochar as a Soil Amendment during Maize Growth: Exploring Practical Alternatives to Recycle Agricultural Residuals and to Reduce Chemical Fertilizer Demand

Abstract: Recycling and value-added utilization of agricultural residues through combining technologies such as anaerobic digestion and pyrolysis could double the recoverable energy, close the nutrient recycle loop, and ensure cleaner agricultural production. This study assessed the beneficial application of biochar to soil to recycle digestate nutrients, improve soil quality, and reduce conventional chemical fertilizer. The addition of digestate-enriched biochar improved soil quality as it provided higher soil organic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
106
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(144 citation statements)
references
References 66 publications
4
106
1
Order By: Relevance
“…Chemical adsorption is considered as the second most influential parameter for water holding capacity of the biochar (Batista et al 2018;Kizito et al 2019). Between 600-2 and 800-1 products, 800-1 showed the significant increase in BET surface area, no difference in TPV (Fig.…”
Section: Increase In Water Holding Capacitymentioning
confidence: 99%
“…Chemical adsorption is considered as the second most influential parameter for water holding capacity of the biochar (Batista et al 2018;Kizito et al 2019). Between 600-2 and 800-1 products, 800-1 showed the significant increase in BET surface area, no difference in TPV (Fig.…”
Section: Increase In Water Holding Capacitymentioning
confidence: 99%
“…In general, increased soil CEC gained by the application of biochar, due to its structural properties such as porous structure, large surface area and negative surface charge, tends to strengthen the retention of K and enable the slow release of nutrients [105]. Kizito et al [106] examined the effect of soil application of corn cob and wood biochar saturated with an anaerobic digestate (AD) derived from biomethanol production. They observed that the application of AD-enriched wood biochar to clay loam soil at a rate of 20 t ha −1 increased soil CEC by > 300%, which were accompanied with a significant increase in the soil macronutrient contents including K, and aboveground biomass of cultivated maize plants.…”
Section: Effects Of Biochar As K Fertilisersmentioning
confidence: 99%
“…Biochar application can increase the carbon content in soil and help in carbon sequestration to improve soil and environment quality ( Figure 5). Moreover, biochar can also enrich soil with nutrients by improved recycling [65][66][67]. About more than half of the nitrogen, phosphorus, and potassium can also be recovered [20].…”
Section: Pyrolysismentioning
confidence: 99%